(untitled) (Al-Farooq Journal of Sciences, 2026)
Code-switching between Arabic and English has become a noticeable feature of contemporary Arab T.V discourse. This paper is going to examine the use of English lexical items by television presenters and commentators in sport, cooking, and beauty programs, including penalty, performance, carnival, pasta, contouring, highlighter, and serum. Therefore, using a qualitative sociolinguistic approach and drawing on Baker’s (2010) framework, the paper explores the functions of code-switching and its relationship to linguistic competence and linguistic dominance. The findings indicate that presenters and commentators frequently use English terms despite the availability of Arabic equivalents. Such language choices are often associated with professional expertise, prestige, modernity, and globalization. The paper concludes that code-switching serves as a communicative strategy for constructing professional identity while also reflecting the growing influence of English in Arabic media discourse.